tert-Butyl 2-de-oxy-4,5-O-isopropyl-idene-d-gluconate. - Jenkinson, S; Booth, K; Best, D; Fleet, G; Watkin, D (2008)
The relative configuration of tert-butyl 2-de-oxy-4,5-O-iso-propyl-idene-d-gluconate, C(13)H(24)O(6), an inter-mediate in the synthesis of 2-de-oxy sugars, was determined by X-ray crystallography, and the crystal structure consists of chains of O-H⋯O hydrogen-bonded mol-ecules running parallel to the a axis. There are two mol-ecules in the asymmetric unit. The absolute configuration was inferred from the use of d-erythrono-lactone as the starting material.